An Investigation of the Magnetic and Structural Characteristics of Li-Ni ferrite nanoparticles - Ebtihal Khidher (Al-Kitab Journal for Pure Sciences)
Nanoparticles of Li-Ni ferrite (LiNi₀.₅Fe₂O₄) were synthesized through the sol-gel auto combustion method, employing lithium nitrate, nickel nitrate, and ferric nitrate as precursors, with citric acid acting as a chelating agent. The samples were annealed at temperatures (as-burnt, from 400 to 800 °C). The impact of various calcination temperatures on the crystalline structure and magnetic characteristics of the LiNi₀.₅Fe₂O₄ nanoparticles was meticulously investigated through X-ray diffraction (XRD) and a vibrating sample magnetometer (VSM).